Accuracy of ICD-9-coded chief complaints and diagnoses for the detection of acute respiratory illness. - Espino, J. U. (American Medical Informatics Association, 2001)
ICD-9-coded chief complaints and diagnoses are a routinely collected source of data with potential for use in public health surveillance. We constructed two detectors of acute respiratory illness: one based on ICD-9-coded chief complaints and one based on ICD-9-coded diagnoses. We measured the classification performance of these detectors against the human classification of cases based on review of emergency department reports. Using ICD-9-coded chief complaints, the sensitivity of detection of acute respiratory illness was 0.44 and its specificity was 0.97. The sensitivity and specificity using ICD-9-coded diagnoses were no different. These properties of excellent specificity and moderate sensitivity, coupled with the earliness and electronic availability of such data, support the use of detectors based on ICD-9 coding of emergency department chief complaints in public health surveillance.